Characterization and Simulation of an Active Microvalve for Glaucoma - Sassetti, Fernando (2011)
Glaucoma drainage device (GDD) has the potential to eliminate hypotony but still suffers from poor flow control and fibrosis. The ideal shunt should change its hydraulic resistance to achieve the desired intraocular pressure (IOP). In this study, the characterisation of a preliminary design of a new GDD is presented. This is activated by means of a diaphragm, which is actuated by conducting polymers. The valve can be manufactured employing microelectromechanical system technology by soft lithography. The characterisation process is performed by numerical simulation using the finite element method, considering the coupling between the fluid and the structure (diaphragm) obtaining the hydraulic resistance for several positions of the diaphragm. To analyse the hydraulic system of the microvalve implanted in a human eye, an equivalent circuit model was used. The parameters of the equivalent circuit model were obtained from numerical simulation. The hydraulic resistance of the designed GDD varies in the range of 13.08–0.36mmHgmin/ml compared with 3.38– 0.43mmHgmin/ml for the Ahmed valve. The maximum displacement of the diaphragm in the vertical direction is 18.9 mm, and the strain in the plane is 2%. The proposed preliminary design allows to control the IOP by varying the hydraulic resistance in a greater range than the existing passive valves, and the numerical simulation facilitates the characterisation and the improvement of the design before its construction, reducing time and costs.